Geophysical Contribution in the Characterization of Deep Water Tables Geometry (Sidi Bouzid, Central Tunisia) - D. Khazri; H. Gabtni (International Journal of Geophysics)
Geophysical data combined with geological and hydrogeological data were analyzed to characterize the geometry of Oued El Hajel and Ouled Asker deep water tables (Sidi Bouzid). The obtained results allowed refining the geostructural schema by highlighting the individualization of the NE-SW underground convexity of Ouled Asker and the anticline of axis Es Souda-Hmaeima and Ezaouia on either sides of two hydrogeological thresholds. The geometrical analysis determined the spatial extension of Ouled Asker and Oued El Hajel subbasins. The seismic cartography of semideep and deep reservoirs (Oligo-Miocene; Eocene and upper Cretaceous) associated with the main subbasins contributed to proposing hydrogeological prospect zones for a rationalized groundwater exploitation.